Case Report: Dupilumab Successfully Controls Severe Eczema in a Child With Elevated IgE Levels and Recurrent Skin Infections - Joshi, Tejas P.; Anvari, Sara; Gupta, Meera R.; Davis, Carla M.; Hajjar, Joud (Frontiers in Pediatrics, 2021)
The efficacy of dupilumab in pediatric patients with severe eczema presenting in the setting of elevated immunoglobulin E (IgE) levels and recurrent bacterial skin infections is not well-understood. Here we present the case of a child with elevated IgE levels in whom dupilumab treatment led to remarkable control of his eczema and recurrent skin infections. We also review the use of dupilumab in other patients with molecularly proven cases of hyper IgE (HIGE) syndrome. Our case supports the notion that dupilumab may have a seminal application in treating severe eczema that occurs in the setting of elevated IgE levels and recurrent bacterial skin infections.